2002
DOI: 10.1007/s004010100437
|View full text |Cite
|
Sign up to set email alerts
|

Sural nerve T cells in demyelinating polyneuropathy associated with monoclonal gammopathy

Abstract: The clinical presentation of polyneuropathy associated with monoclonal gammopathy is heterogeneous. As T cells in sural nerve biopsy specimens may represent a marker of inflammation, we analyzed whether the presence of sural nerve T cells in patients with demyelinating polyneuropathy associated with monoclonal gammopathy may help to define a specific clinical entity. Using immunohistochemical analysis we investigated the number and distribution of sural nerve T cells in 18 patients with polyneuropathy associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“… 155 Immunohistochemistry can add diagnostic and prognostic value. 118 , 159 , 160 One study found that EM added value in about 14% of cases. 155 Diagnostic yield for pathologies known to have patchy involvement would be expected to improve with larger amount of nerve tissue for examination.…”
Section: Methodsmentioning
confidence: 99%
“… 155 Immunohistochemistry can add diagnostic and prognostic value. 118 , 159 , 160 One study found that EM added value in about 14% of cases. 155 Diagnostic yield for pathologies known to have patchy involvement would be expected to improve with larger amount of nerve tissue for examination.…”
Section: Methodsmentioning
confidence: 99%